Islam and secularism in Turkey : Kemalism, religion and the nation state - Azak, Umut (International library of twentieth century history, 2010)
Kemal Ataturk's Republic of Turkey was set up in 1923 as a secular state, sweeping political, social, cultural and religious reforms followed. Islam was no longer the official religion of the state, the Sultanate was abolished and all Turkish citizens were declared equal without reference to religion. But though, in Azak's phrase, 'secularism was the central tenet of Kemalism', fear of a resurgent, even fanatical, Islam, continued to haunt the state. Azak's revisionist and original study sets out the struggle between religion and secularism but shows how Ataturk laboured for an idealised 'Turk.